The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/chem.200305179
|View full text |Cite
|
Sign up to set email alerts
|

Computational Approaches to Activity in Rhodium‐Catalysed Hydroformylation

Abstract: In this theoretical study on rhodium-catalysed hydroformylation we examine an unmodified hydridorhodium(I) carbonyl system a together with three variants modified by the model phosphane ligands PF3 (system b), PH3 (system c) and PMe3 (system d), which show increasing basicity on the Tolman chi parameter scale. The olefinic substrate for all systems is ethene. Based on the dissociative hydroformylation mechanism, static and dynamic quantum-mechanical approaches are made for preequilibria and the whole catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
48
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 64 publications
(74 reference statements)
6
48
1
Order By: Relevance
“…[60] Thus, a reaction through the sterically crowded path I could not be prevented during alkene insertion but during alkene coordination. Unfortunately, it is unclear whether a high kinetic barrier exists for the formation of one or more isomers of the styrene complex before alkene insertion.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…[60] Thus, a reaction through the sterically crowded path I could not be prevented during alkene insertion but during alkene coordination. Unfortunately, it is unclear whether a high kinetic barrier exists for the formation of one or more isomers of the styrene complex before alkene insertion.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Most of the work has been reviewed, [11][12][13] but several aspects of hydroformylation are still under investigation. [14][15][16][17][18][22][23][24] The entire catalytic cycle for rhodium/ phosphane-catalyzed hydroformylation has been examined at different levels of calculation by using simplified model phosphanes and ethene as model alkene. [14][15][16] Recently, Rocha and Almeida used propene instead of ethene as substrate to investigate the regioselectivity on HRh(CO)(PH 3 ) 2 model rhodium/phosphane catalysts, [17a] and on HRh(CO) 3 unmodified rhodium catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In line with these arguments, recent high-level calculations on related model systems showed that barriers for alkene association/ dissociation are negligible, and when free-energy corrections are considered, alkene complexes and their dissociation products are almost isoenergetic. [14] Substrate-ligand interactions: To more deeply analyze the factors governing enantioselectivity, we investigated ligandsubstrate interactions in more detail. We stated above that the difference between phenyl-phenyl and phenyl-methyl interactions may be crucial in sterodifferentiation.…”
mentioning
confidence: 99%
“…Indeed, previous theoretical studies on the hydride migration step of the hydroformylation reaction have shown that the geometry of the transition state is far from linear. [15][16][17][18][19][20] Furthermore, because the hydride migration step in the hydroformylation reaction involves the breaking of a rhodium À hydride bond, which is significantly different from a carbon À hydrogen bond, interpretations purely based on a single small 1 H/ 2 H kinetic isotope effect can be misleading. A more detailed discussion is provided below.…”
mentioning
confidence: 96%